Safety of Normothermic Cardiopulmonary Bypass in Pediatric Cardiac Surgery: A System Review and Meta-Analysis - Xiong, Tao; Pu, Lei; Ma, Yuan-Feng; Zhu, Yun-Long; Cui, Xu; Li, Hua; Zhan, Xu; Li, Ya-Xiong (Frontiers in Pediatrics, 2021)
Objectives: Hypothermic cardiopulmonary bypass (HCPB) has been used successfully in cardiac surgery for more than half a century, although adverse effects have been reported with its use. Many studies on temperature management during CPB published to date have shown that normothermic CPB (NCPB) provides more benefits to children undergoing cardiac surgery. The present meta-analysis investigated the effect of NCPB on clinical outcomes based on results of randomised controlled trials and observational studies on paediatric cardiac surgery. Methods: Databases such as PubMed, EMBASE, Cochrane Central Register of Controlled Trials, and Clinical Trials.gov were searched from inception to May 2021 to identify relevant studies published in English. Results: The present meta-analysis included 13 studies characterising a total of 837 paediatric patients. The random effects model exhibited that the NCPB group had reduced revision for postoperative bleeding [odds ratio (OR): 0.11; 95% confidence interval (CI): 0.01–0.89; I2 = 0%, P = 0.04], serum lactate 2–4 h after CPB (mean difference: −0.60; 95% CI: −1.09 to −0.11; I2 = 82%, P = 0.02), serum creatinemia 24 h after CPB (mean difference: −2.73; 95% CI: −5.06 to −0.39; I2 = 83%, P = 0.02), serum creatinemia 48 h after CPB (mean difference: −2.08; 95% CI: −2.78 to −1.39; I2 = 0%, P < 0.05), CPB time (mean difference: −19.10, 95% CI: −32.03 to −6.18; I2 = 96%, P = 0.04), and major adverse events (OR: 0.37; 95% CI: 0.15–0.93; Z = 2.12, P = 0.03) after simple congenital surgery compared with the HCPB group. Conclusion: NCPB is as safe as HCPB in paediatric congenital heart surgery. Moreover, NCPB provides more advantages than HCPB in simple congenital heart surgery.